Connected pathway relative permeability from pore-scale imaging of imbibition. (April 2016) - Berg, S.; Rücker, M.; Ott, H.; Georgiadis, A.; van der Linde, H.; Enzmann, F.; Kersten, M.; Armstrong, R.T.; de With, S.; Becker, J.; Wiegmann, A.
Highlights: Quasi-static simulation of two-phase flow in porous media agrees with experimental data within experimental uncertainty for drainage. A morphological approach, which approximates capillary displacement, does not represent the imbibition process. Ultimately for modeling relative permeability in imbibition an approach is needed that captures moving liquid-liquid interfaces which requires viscous and capillary forces simultaneously. If pore scale fluid distributions are available e.g. from micro-CT flow experiments, relative permeability can be estimated from the connected pathway flow (for low capillary numbers). The agreement is better at low water saturations where the oil phase is predominantly connected than at higher water saturation where the oil phase is increasingly disconnected. Abstract: Pore-scale images obtained from a synchrotron-based X-ray computed micro-tomography (µCT) imbibition experiment in sandstone rock were used to conduct Navier–Stokes flow simulations on the connected pathways of water and oil phases. The resulting relative permeability was compared with steady-state Darcy-scale imbibition experiments on 5 cm large twin samples from the same outcrop sandstone material. While the relative permeability curves display a large degree of similarity, the endpoint saturations for the µCT data are 10% in saturation units higher than the experimental data. However, the two datasets match well when normalizing to the mobile saturation range. The agreement is particularly good at low water saturations, where the oil is predominantly connected. Apart from different saturation endpoints, in this particular experiment where connected pathway flow dominates, the discrepancies between pore-scale connected pathway flow simulations and Darcy-scale steady-state data are minor overall and have very little impact on fractional flow. The results also indicate that if the pore-scale fluid distributions are available and the amount of disconnected non-wetting phase is low, quasi-static flow simulations may be sufficient to compute relative permeability. When pore-scale fluid distributions are not available, fluid distributions can be obtained from a morphological approach, which approximates capillary-dominated displacement. The relative permeability obtained from the morphological approach compare well to drainage steady state whereas major discrepancies to the imbibition steady-state experimental data are observed. The morphological approach does not represent the imbibition process very well and experimental data for the spatial arrangement of the phases are required. Presumably for modeling imbibition relative permeability an approach is needed that captures moving liquid-liquid interfaces, which requires viscous and capillary forces simultaneously. Graphical abstract: